2020
DOI: 10.2217/epi-2019-0404
|View full text |Cite
|
Sign up to set email alerts
|

Circrna Hsa_Circ_0004771 Promotes Esophageal Squamous Cell Cancer Progression Via miR-339-5p/CDC25A Axis

Abstract: Aim: The role of circRNAs in esophageal squamous cell cancer (ESCC) remains unclear. Materials & methods: Here we profiled six pair plasma circRNA in ESCC based on RNA sequencing, and then verified the elevation of hsa_circ_0004771 in 20 cancer tissues and 105 pair case–control plasma samples by quantitative reverse transcriptase PCR. Results: The upregulation of hsa_circ_0004771 was correlated with heavier tumor burden and poor prognosis, knockdown of it inhibited the ESCC cells proliferation bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Libraries were controlled for quality and quantified using the BioAnalyzer 2100 system (Agilent Technologies, Inc., USA). Library sequencing was performed on an illumina Hiseq instrument with 150 bp paired end reads [16].…”
Section: Rna-sequencing and Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Libraries were controlled for quality and quantified using the BioAnalyzer 2100 system (Agilent Technologies, Inc., USA). Library sequencing was performed on an illumina Hiseq instrument with 150 bp paired end reads [16].…”
Section: Rna-sequencing and Bioinformaticsmentioning
confidence: 99%
“…As shown in Fig 3A, the expression of ASC as inflammasome adaptor protein was significantly increased (1.78±0.29 versus 1.01±0. 16 [control], P<0.001). Furthermore, compared to the control group, the mRNA abundance of caspase-1 was significantly higher in the fetal membranes of TPROM patients (2.69±0.31 versus 1.05±0.27 [control], P<0.001) ( Fig 3B).…”
Section: Nlrc4 Inflammasomes Activation Participates In Tprom Processmentioning
confidence: 99%
“…Overexpression of circ-SLC7A5 in ESCC plasma samples was correlated with TNM stage and poor OS (Wang Q. et al, 2020). Elevated circ-0004771 levels were associated with heavier tumor burden and poor prognosis (Huang E. et al, 2020). Circ_0067934 was upregulated in ESCC tissues and its increased expression correlated with poor differentiation, I-II T stage, and I-II TNM stage (Zong et al, 2018b).…”
Section: Head and Neck Squamous Cell Cancer (Hnscc)mentioning
confidence: 99%
“…The expression of circ_0004771 was up-regulated in plasma and tissues of patients with EC. QRT-PCR verification and ROC curve analysis showed that circ_0004771 had higher significance and better diagnostic value, and its expression level was significantly correlated with T grade (invasion of the primary tumor range) and vascular invasion, suggesting that circ_0004771 can be used as an index to judge the prognosis [35]. At present, carcinoembryonic antigen (CEA) is one of the most commonly used diagnostic markers for EC [36].…”
Section: Circrnas As Biomarkers In Ecmentioning
confidence: 99%
“…Compared with paracancerous tissues, the expressions of hsa_circ_0067934, circFNDC3B, circ-TTC17, hsa_circ_0006168, circPVT1 and hsa_circ_100873 were significantly up-regulated in EC tissues [ 39 , 40 , 42 , 43 , 56 , 57 ]. So far, cir-ITCH, circ-PRKCI, circRAD23B, cZNF292, circ-Foxo3, circGSK3 β, circLARP4 and hsa_circ_0004771 have been shown to regulate the proliferation and apoptosis of EC cells through different signal pathways [ 35 , 37 , 50 , 58 62 ]. In a word, different results suggest that circRNAs may promote or inhibit development of EC through different mechanisms (Fig.…”
Section: Role and Significance Of Circrnas In Ecmentioning
confidence: 99%